A palette of background-free tame fluorescent probes for intracellular multi-color labelling in live cells. Issue 8 (2nd February 2018) - Alamudi, Samira Husen; Su, Dongdong; Lee, Kyung Jin; Lee, Jung Yeol; Belmonte-Vázquez, José Luis; Park, Hee-Sung; Peña-Cabrera, Eduardo; Chang, Young-Tae
Abstract : A palette of background-free tame fluorescent probes were designed and applied to intracellular multi-color labelling in live cells. Abstract : A multi-color labelling technique for visualizing multiple intracellular apparatuses in their native environment using small fluorescent probes remains challenging. This approach requires both orthogonal and biocompatible coupling reactions in heterogeneous biological systems with minimum fluorescence background noise. Here, we present a palette of BODIPY probes containing azide and cyclooctyne moieties for copper-free click chemistry in living cells. The probes, referred to as 'tame probes', are highly permeable and specific in nature, leaving no background noise in cells. Such probes, which are rationally designed through optimized lipophilicity, water solubility and charged van der Waals surface area, allow us to demonstrate rapid and efficient concurrent multi-labelling of intracellular target components. We show that these probes are capable of not only labelling organelles and engineered proteins, but also showing the intracellular glycoconjugates' dynamics, through the use of metabolic oligosaccharide engineering technology in various cell types. The results demonstrated in this study thus provide flexibility for multi-spectral labelling strategies in native systems in a high spatiotemporal manner.